Getting Food to the Table: Challenges, Strategies, and Compromises Experienced by Low-Income Veterans Raising Children. Issue 1 (2nd January 2022) - Kamdar, Nipa; True, Gala; Lorenz, Laura; Loeb, Aaron; Hernandez, Daphne C.
ABSTRACT: Using photo-elicitation, 17 low-income, post-9/11 Veterans with children residing in/near Houston, TX shared experiences getting food to their table. Limited money, time, and disabilities challenged access to healthy meals. Limited resources decreased choice and control over what Veterans fed their children. Affordable, accessible food fell below nutritional standards. Veterans rationed their own intake to preserve food for their children. Informed by Veterans' experiences, we developed a model of three factors – resources, personal capacity, and culture – that influence quality, quantity, and type of food low-income Veterans access. Policies to help Veterans increase access to nutritious food need to consider these factors.